1990
DOI: 10.1159/000200218
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin in the Inhibition of Gastric Secretion and Gastric Emptying in Humans

Abstract: Cholecystokinin (CCK) is known to inhibit gastric acid secretion and gastric emptying but its physiological role in the inhibition of gastric functions is not settled. In this study performed on 16 young male subjects, gastric acid secretion and emptying rate were determined after intragastric administration of 8 % peptone meal alone or in combination with intravenous infusion of graded doses of CCK-8 (5–80 pmol/kg·h) or with addition of vegetable oil to meal without or with pretreatment with loxiglumide, a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Though a consequent increase in antral motility and GE of solid food would be expected, it is possible that an increase in gastric acid, gastrin secretion and duodenogastric reflux could cause a reflex decrease in GE, through release of cholecystokinin and secretin 39. It would be invaluable to investigate the role of duodenogastric reflux in the pathogenesis of delayed GE in asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Though a consequent increase in antral motility and GE of solid food would be expected, it is possible that an increase in gastric acid, gastrin secretion and duodenogastric reflux could cause a reflex decrease in GE, through release of cholecystokinin and secretin 39. It would be invaluable to investigate the role of duodenogastric reflux in the pathogenesis of delayed GE in asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…CCK inhibits gastric emptying by relaxing the proximal part of the stomach and stimulating contraction of the pyloric sphincter (Chey et al 1970, Fisher et al 1973. CCK also inhibits gastric secretion in humans (Konturek et al 1990). In this study, hCG treatment of Ovx rats resulted in a fact that the inhibition of gastric emptying induced by hCG might be associated with CCK hypersecretion and that inhibition of gastric emptying caused by hypersecretion of hCG and CCK may explain the gastric distension and NVP seen in women during the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystokinin (CCK), a 33 amino acid peptide extracted from porcine intestine (Jorpes & Mutt 1966), inhibits gastric emptying in animals (Debas et al 1975, Wu et al 2008 and humans (Konturek et al 1990) but has also been reported to stimulate colonic transit in vivo (Dinoso et al 1973, Harvey & Read 1973. The biological actions of CCK are mediated by two types of receptors, CCK 1 and CCK 2 (Noble et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…DU patients, as a group, tend to secrete more acid than normal subjects both at rest and in response to secretory stimulation (1) and this has been attributed mainly to hypergastrinemia and impaired inhibition of gastric functions partly by endogenous cholecystokinin (CCK) possibly due to the failure of this peptide to stimulate somatostatin release from antral D cells (2,3). CCK has been considered as a candidate of an enterogastrone (4), a hormonal substance released by fat in the intestine that causes not only physiological inhibition of gastric secretion (5) but also inhibits gastric emptying (6)(7)(8). Several animal and human studies (8,9) have shown that exogenous CCK as well as endogenous CCK released after feeding inhibits gastric emptying.…”
mentioning
confidence: 99%
“…CCK has been considered as a candidate of an enterogastrone (4), a hormonal substance released by fat in the intestine that causes not only physiological inhibition of gastric secretion (5) but also inhibits gastric emptying (6)(7)(8). Several animal and human studies (8,9) have shown that exogenous CCK as well as endogenous CCK released after feeding inhibits gastric emptying.…”
mentioning
confidence: 99%